The Influence of Artificial Intelligence in Human Resource Management on Employee Performance in the Era of Digital Transformation - Fahmi Kamal (Asosiasi Peneliti dan Inovasi Nusantara (APIN), 2026)
This study aims to analyze the influence of Artificial Intelligence (AI) in Human Resource Management (HRM) on employee performance in the era of digital transformation. The rapid development of digital technologies has encouraged organizations to adopt AI-based HRM systems to improve efficiency, decision-making, and workforce productivity. This research employs a quantitative approach with an explanatory design. Data were collected through structured online questionnaires using a Likert scale from employees working in organizations that implement AI-based HRM systems. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach to test the relationships between variables. The results indicate that AI in HRM has a positive and significant effect on employee performance, both directly and indirectly through digital transformation readiness. AI-driven HR practices enhance recruitment processes, performance management, and employee engagement, leading to improved productivity and organizational effectiveness. The discussion highlights that organizational readiness, technological infrastructure, and human AI collaboration are critical factors in maximizing the benefits of AI implementation. In conclusion, AI-based HRM is a strategic approach that significantly improves employee performance and supports organizational competitiveness in the digital era. Effective implementation requires alignment between technology, human resources, and organizational strategy